PENGARUH WAKTU SADAP DAN UMUR TANAMAN KARET (Havea brasiliensis Muell.Arg) KLON PB340 TERHADAP PRODUKSI LATEKS DI DIVISI I KEBUN TANAH BESIH PT. SOCFINDO - Saroha Manurung; Aulia Juanda; Diki Sapti Purnama (Jurnal Agro Estate, 2018)
The research was conducted in July to August 2017 at Tanah Besih Estate PT. Socfindo. The method used Factorial Design with the treatment age of plant and tapping time. The results of this research show that the treatment eﬀected to latex yield, latex volume, latex drops frequency, lump and scrub weight which are contained on W1 and tapping time was at 04.00 a.m.. Age of plant treatment eﬀected to the latex yield, latex volume, latex drop frequency, lump weight and scrub weight, which are contained on the U1 at the age of 13 years old plants. Interactions treatment between tapping time and age of plant had no eﬀect to the real production of Latex.